2017
DOI: 10.3390/molecules22081276
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Purification and Structural Characterization of Two Novel Water-Soluble Polysaccharides from Anredera cordifolia

Abstract: Anredera cordifolia, a climber and member of the Basellaceae family, has long been a traditional medicine used for the treatment of hyperglycemia in China. Two water-soluble polysaccharides, ACP1-1 and ACP2-1, were isolated from A. cordifolia seeds by hot water extraction. The two fractions, ACP1-1 and ACP2-1 with molecular weights of 46.78 kDa ± 0.03 and 586.8 kDa ± 0.05, respectively, were purified by chromatography. ACP1-1 contained mannose, glucose, galactose in a molar ratio of 1.08:4.65:1.75, whereas ACP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
(56 reference statements)
1
21
0
1
Order By: Relevance
“…The myostatin gene activates Smad2 signaling and inhibits Akt activation, thereby altering the expression of multiple genes involved in the regulation of protein degradation and increasing skeletal muscle apoptosis [ 9 , 72 , 73 ]. Previous studies on ROS-related factors inducing myoblast apoptosis have shown that the p53 and Akt pathways are involved in cell apoptosis and ROS accumulation [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The myostatin gene activates Smad2 signaling and inhibits Akt activation, thereby altering the expression of multiple genes involved in the regulation of protein degradation and increasing skeletal muscle apoptosis [ 9 , 72 , 73 ]. Previous studies on ROS-related factors inducing myoblast apoptosis have shown that the p53 and Akt pathways are involved in cell apoptosis and ROS accumulation [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…To each 1.5 mL centrifuge tube, 0.3 mol/L NaOH and 0.5 mol/L 1-phenyl-3-methyl-5-pyrazolone (PMP) solution (Sigma-Aldrich, Prefecture, MO, USA) were added to produce the derivative. After neutralization with 0.3 mol/L HCl, chloroform extraction was carried out several times and then the sample was centrifuged to retain the supernatant, which was used for liquid chromatography [31,38,39].…”
Section: Methodsmentioning
confidence: 99%
“…They are the potential sources of complex phytoconstituents. Selaginella kraussiana (African club moss) [11], Lonicera japonica (Japnese honeysuckle) [32], Eriobotrya japonica (Loquat) [35] and Anredera cordifolia (Mignonette vine) [38] contains polysaccharides. Alternanthera philoxeroides (Alligator weed) [13] and Rhamnus alaternus (Evergreen buckthorn) [26] contains anthraquinone glycosides.…”
Section: Chemical Profi Le Of Weeds Established In New Zealandmentioning
confidence: 99%